Human Resource Management Model of Islamic Boarding Schools Based on the Values ​​of Service and Tahfizul Qur'an: A Study at the Assa'idiyyah Gedongan Islamic Boarding School in Cirebon - Muhammad Ni’amillah; Dewi Cahyani; Moh Ali (al-Afkar, Journal For Islamic Studies, 2026)
The dynamic shifts within the contemporary educational landscape necessitate that pesantren (Islamic boarding schools) adopt a more focused and professional approach to Human Resource Management (HRM). This challenge must be met without sacrificing the fundamental values that constitute the institution’s unique identity and core characteristic. In this context, the values of khidmah (selfless service/devotion) and tahfizhul Qur’an (Qur'an memorization) remain strong cultural and spiritual foundations, directly shaping the character, work ethic, and loyalty of the teachers and administrative staff within the pesantren. This article aims to thoroughly examine how the integration of these two fundamental values, khidmah and tahfizhul Qur’an, can be realized and operationalized into a cohesive and comprehensive model of pesantren Human Resource Management. The study focuses on proposing a value-driven framework that balances spiritual principles with professional administrative governance.